ANALISIS AKUNTANSI ZAKAT BERDASARKAN PSAK NO.109 PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) SUMATERA UTARA - Pandapotan Ritonga (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2016)
The purpose of this study was to determine whether the accounting treatment of zakat on BAZNAS North Sumatra in accordance with SFAS No. 109. This study was conducted to examine the financial statements prepared BAZNAS North Sumatra and to determine the application of zakat, sadaqah infaq and in accordance with SFAS No. 109, Accounting for Zakat. The method used is the method descriptive approach and this type of data is qualitative From the results of this study concluded that BAZNAS North Sumatra have not fully implemented the use of SFAS 109 in the present financial statements. Because under SFAS No. 109, accounting for zakat aims to regulate the recognition, measurement, presentation and disclosure of transactions zakat, infaq / Sadaqah